Dramatic Results for IUCEE in Private Colleges of State of Maharashtra in the Western Region of India - Nandurkar, K. N.; Kulkarni, Sushama (Journal of Engineering Education Transformations, 2010)
The state of Maharashtra has shown that dramatic results can be achieved in their private engineering colleges. Maharashtra had. most of its J 85 participants from private engineering colleges. Faculty have shown their resourcefulness in fallowing up with significant activities and results after 2008 Faculty Leadership Institutions (FLI).